IMPLEMENTASI PROGRAM JUMPA BERKAH UNTUK MEMBENTUK KARAKTER DISIPLIN DAN TANGGUNG JAWAB PADA SISWA DI MIM NGADIREJAN - Putri Purmitasari; Itsnaini Muslimati Alwi (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to analyze the implementation of the Jumpa Berkah Program in shaping students discipline and responsibility at MIM Ngadirejan. The research uses a qualitative descriptive approach through field study. The subjects include the principal, Islamic Education teachers, and upper-grade students selected through purposive and snowball sampling techniques. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman model. The results show that the Jumpa Berkah Program, which is routinely carried out through activities such as congregational dhuha prayer, recitation of Asmaul Husna, short surah recitation, and charity (infaq), is able to build positive habits among students. Students become more disciplined in participating in activities and more responsible in carrying out tasks without constant reminders. In addition, the program also fosters students’ religious practices and social awareness. The success of the program is supported by the active role of teachers as role models and institutional support, although there are still challenges related to limited facilities. Overall, this program is effective as a habituation-based approach to character building.